2015
DOI: 10.1016/j.mser.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Losses in ferroelectric materials

Abstract: Ferroelectric materials are the best dielectric and piezoelectric materials known today. Since the discovery of barium titanate in the 1940s, lead zirconate titanate ceramics in the 1950s and relaxor-PT single crystals (such as lead magnesium niobate-lead titanate and lead zinc niobate-lead titanate) in the 1980s and 1990s, perovskite ferroelectric materials have been the dominating piezoelectric materials for electromechanical devices, and are widely used in sensors, actuators and ultrasonic transducers. Ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(124 citation statements)
references
References 319 publications
(315 reference statements)
6
118
0
Order By: Relevance
“…In 2014 an experimental investigation was carried out to harvest energy by using piezoelectric generator over wide range of frequency and optimal load resistance [11]. Mechanical quality factor helps in designing of a sensor and actuator and it is one of the most important parameter to determine the energy loss characteristic of piezoelectric material [12,13].The range of the mechanical quality factor (Q m ) varies from 3700 at 158 kHz frequency to 930 at 1.18 MHz frequency [14]. A study reported a new class of piezoelectric materials having high mechanical quality factor which vibrate at 1.7MHz and have a lot of applications as sensor and actuator [15].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…In 2014 an experimental investigation was carried out to harvest energy by using piezoelectric generator over wide range of frequency and optimal load resistance [11]. Mechanical quality factor helps in designing of a sensor and actuator and it is one of the most important parameter to determine the energy loss characteristic of piezoelectric material [12,13].The range of the mechanical quality factor (Q m ) varies from 3700 at 158 kHz frequency to 930 at 1.18 MHz frequency [14]. A study reported a new class of piezoelectric materials having high mechanical quality factor which vibrate at 1.7MHz and have a lot of applications as sensor and actuator [15].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…22, With the synthesis conditions described above, the grain sizes are found to be extremely small, and may give rise to resistive and capacitive grain boundaries. As improved elsewhere, 23,24 the dielectric loss appears to be a strong function of grain size. Thus, the decrease in loss can be understood from the fact that the lower conductivity of the fine-grained ceramics is due to the higher density of resistive grain boundaries.…”
Section: Resultsmentioning
confidence: 53%
“…c 44 of KNLNST cannot be measured for the lack of single domain sample. According to our precious work, c E 44 and c E 55 of single domain orthorhombic KNN-based crystal are 7.80 Â 10 10 and 1.90 Â 10 10 N/m 2 , respectively, more than 5 times larger than those of the Pbbased crystals with the same domain structure (c E 44 ¼ 1.28 Â 10 10 and c E 55 ¼ 0.32 Â 10 10 N/m 2 ). 25,26 So, we may conclude that in the tetragonal phase, c 44 of KNLNST should be much larger than that of the Pb-based crystals.…”
mentioning
confidence: 90%
“…7,8 The extrinsic contribution plays a critical role in various functionalities, such as dielectric properties, piezoelectric activity, and energy loss behavior. 9,10 In addition, understanding the mechanism of domain wall motions is very helpful to get some insight into the nonlinearity, frequency dispersion, and aging of physical properties. 11 For the investigation of domain structures, single crystals are preferred over ceramics because dynamic process of domain evolution with E filed and temperature can be easily observed in single crystals.…”
mentioning
confidence: 99%